Pharmacokinetic Assessment of the Uptake of 16β-[(18)F]-Fluoro-5α Dihydrotestosterone (FDHT) in Prostate Tumors as Measured by PET - Beattie, Bradley J. (2010)
OBJECTIVE: The aim of this study was to develop a clinically applicable non-invasive method to quantify changes in androgen receptor (AR) levels based on (18)F-FDHT PET in prostate cancer patients undergoing therapy. METHODS: Thirteen patients underwent dynamic (18)F-FDHT PET scans over a selected tumor. Concurrent venous blood samples were acquired for blood metabolite analysis. A second cohort of 25 patients, injected with (18)F-FDHT underwent dynamic PET imaging of the heart. These data were used to generate a population-based input function, essential for pharmacokinetic modeling. Linear compartmental pharmacokinetic models of increasing complexity were tested on the tumor tissue data. Four suitable models were applied and compared using the Bayesian Information Criterion (BIC). Model 1 consisted of an instantaneously equilibrating space followed by a unidirectional trap. Models 2a and 2b contained a reversible space between the instantaneously equilibrating space and the trap, into which metabolites were excluded (2a) or allowed (2b). Model 3 built upon Model 2b with the addition of a second reversible space preceding the unidirectional trap and from which metabolites were excluded. RESULTS: The half-life of the (18)F-FDHT in blood was determined to be between 6-7 minutes. As a consequence, the uptake of (18)F-FDHT in prostate cancer lesions reached a plateau within 20-minutes as the blood-borne activity was consumed. Radiolabeled metabolites were shown not to bind to AR in in-vitro studies with CWR22 cells. Model 1 produced reasonable and robust fits for all datasets and was judged best by the BIC for 16 out of 26 tumor scans. Models 2a, 2b and 3 were judged best in seven, two and one case, respectively. CONCLUSION: Our study explores the clinical potential of using (18)F-FDHT PET to make estimates of free AR concentration. This process involved the estimation of a net-uptake parameter such as Model 1’s k(trap) that could serve as a surrogate measure of AR expression in metastatic prostate cancer. Our initial studies suggest a simple body-mass normalized standard uptake value (SUV) is reasonably well correlated to model based k(trap) estimates, which we surmise may be proportional to AR expression. Validation studies to test this hypothesis are underway.